New experimental measurements of the H2-CO2 Collision-Induced Absorption in the [3907, 4770] cm−1 spectral range from 241 to 498 K - F. Vitali; S. Stefani; G. Piccioni; H. Tran; M. Snels; D. Grassi; C. Boulet; D. Biondi; A. Boccaccini (Icarus, 2026)

Exposure assessment to waste anesthetic isoflurane during large-animal surgery: Environmental, personal and biological monitoring - Mariana G. Braz; Tony F. Grassi; Maria Vitória Destro; Francisco J. Teixeira-Neto; Leandro G. Braz (Environmental Toxicology and Pharmacology, 2026)

Evaluation of genetic instability in patients with amyotrophic lateral sclerosis - Hendrew J.B.C. Souza; Kátina M. Souza; Matheus B. dos Santos; Mariane A.P. Silva; Tony F. Grassi; Maria V. Destro; Mariana G. Braz (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2026)

A simulator of the MAJIS instrument onboard the JUICE mission: Description and application to operational and scientific cases - C. Royer; P. Haffoud; Y. Langevin; F. Poulet; D. Bockelée-Morvan; E. D’Aversa; M. Cisneros-González; D. Grassi; N. Ligier; G. Piccioni; J. Carter; F. Tosi; et al. (Planetary and Space Science, 2025)

Effects of antibiotics and metals on meiofauna assessed through taxon/functional and modeling tools: a case study of amoxicillin and copper - Sahar Ishak; Samir Ghannem; Renad M. Alotaibi; Rahaf S. Alkatheri; Mona F. Alharbi; Alanood M. Almutrif; Eleonora Grassi; Federica Semprucci; Riadh Badraoui; Sunakbaeva Dilara; Naoufel Ben Hamadi; Lotfi Khezami; et al. (Marine Pollution Bulletin, 2025)

Exploring the effects of decabromodiphenyl ether on meiofaunal communities: An experimental approach - E. Grassi; M. Greco; L. Guidi; M. Pasquariello; E. Al-Enezi; M. Trifuoggi; F. Frontalini; F. Semprucci (Marine Pollution Bulletin, 2025)

Environmental and biological measurements of the anesthetic isoflurane and its possible toxic effects in veterinarians - Tony F. Grassi; Mariane A.P. Silva; Maria V. Destro; Bruno S. De Martinis; Leandro G. Braz; Mariana G. Braz (Environmental Toxicology and Pharmacology, 2025)

Deformed archaeological remains at Lilybaeum in Western Sicily (southern Italy): possible ground signatures of a missed large earthquake - G. Barreca; F. Pepe; A. Sulli; G. Morreale; S. Gambino; M. Gasparo Morticelli; S. Grassi; C. Monaco; S. Imposa (Natural Hazards, 2025)
Archaeoseismic analysis performed in Western Sicily points to deformed archeological remains at Lilybaeum , a Punic coastal city founded in 397 B.C. at the Island’s westernmost edge. Starting from the direct observation of deformed ruins, an interdisciplinary work strategy, which included field-structural analysis, drone-shot high-resolution aerial photogrammetry, and geophysical prospecting, was employed to investigate whether the identified deformations may represent the ground effects of a previously unknown large earthquake in the area. Among the unearthed remains, some mosaics and a stone-paved monumental avenue show evidence of tectonic deformation, being fractured, folded, and uplifted. The trend of folding and fracturing is consistent with the NNW–SSE oriented tectonic max stress axis to which Western Sicily is currently subjected. Displacement along a fracture deforming the Decumanus Maximus together with the finding of a domino-type directional collapse, enable us to interpret the observed deformation as the ground signature of a coseismic slip. The seismic rupture occurred along a previously unmapped deformation front that fits well within the seismotectonic context of Western Sicily. Measured offset, geophysical prospecting, and age-constraints all suggest the possibility that a highly-energetic earthquake nucleated in the area following a coseismic rupture along a NE–SW trending back-verging reverse fault towards the end of the fourth century CE. Since seismic catalogs do not provide evidence of such a large earthquake, this event might represent a missed entry in the historical seismic record. This finding provides constraints to redefine the seismic hazard of Western Sicily, a region where recurrence-time intervals for large earthquakes are still unknown.

How natural and anthropogenic factors should drive microplastic behavior and fate: The scenario of Brazilian urban freshwater - Fernando F. Sodré; Imisi M. Arowojolu; Maria C. Canela; Rodrigo S. Ferreira; Andreia N. Fernandes; Cassiana C. Montagner; Cristiane Vidal; Mariana A. Dias; Gilberto Abate; Leticia C. da Silva; Marco T. Grassi; Crislaine Bertoldi; et al. (Chemosphere, 2023)

Critical metal geochemistry in groundwaters influenced by dredged material - Aaron J. Goodman; Austin Scircle; Ashley Kimble; William Harris; Bailey Calvitti; Daniel Sirkis; Leanne Mathurin; Vincent Grassi; James F. Ranville; Anthony J. Bednar (Science of The Total Environment, 2023)

Preparation of carbonaceous materials from flotation-sludge of the poultry industry and its application in the methylene blue adsorption - Angélica F. M. Streit; Patrícia Grassi; Fernanda C. Drumm; Luis F. O. Silva; Marcos L. S. Oliveira; Gabriela C. Collazzo; Marcelo Godinho; Daniele Perondi; Guilherme L. Dotto (Environmental Science and Pollution Research, 2023)

Conversion of foliar residues of Sansevieria trifasciata into adsorbents: dye adsorption in continuous and discontinuous systems - Patrícia Grassi; Matias Schadeck Netto; Sérgio Luiz Jahn; Jordana Georgin; Dison S. P. Franco; Mika Sillanpää; Lucas Meili; Luis F. O. Silva (Environmental Science and Pollution Research, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

A quick combined approach for the characterization of a cliff during a post-rockfall emergency - G. Pappalardo; S. Mineo; S. Imposa; S. Grassi; A. Leotta; F. La Rosa; D. Salerno (Landslides, 2020)

Role of Mycobacterium avium lysate INF-γ, IL-17, and IL-2 ELISPOT assays in diagnosing nontuberculous mycobacteria lymphadenitis in children - Chiara Della Bella; Elisabetta Venturini; Savannah Devente; Paola Piccini; Simona Tapinassi; Leila Bianchi; Alessia Grassi; Marisa Benagiano; Heba F. Mustafa Alnwaisri; Carlotta Montagnani; Elena Chiappini; Wilbert Bitter; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Association Between the Serum Uric Acid Levels and Lacunar Infarcts in the Elderly - F. Crosta; U. Occhiuzzi; G. Passalacqua; E. Occhiuzzi; A. Cimini; D. Grassi; C. Ferri; C. Marini; C. Borghi; G. Desideri (Journal of Molecular Neuroscience, 2018)

The Motor KIF5C Links the Requirements of Stable Microtubules and IGF-1 Receptor Membrane Insertion for Neuronal Polarization - Mariana Oksdath; Alvaro F. Nieto Guil; Diego Grassi; Lucas J. Sosa; Santiago Quiroga (Molecular Neurobiology, 2017)

Geophysical surveys to study a landslide body (north-eastern Sicily) - S. Imposa; S. Grassi; F. Fazio; G. Rannisi; P. Cino (Natural Hazards, 2017)

The adipose tissue and the involvement of the renin–angiotensin–aldosterone system in cardiometabolic syndrome - F. Borghi; B. Sevá-Pessôa; D. M. Grassi-Kassisse (Cell and Tissue Research, 2016)

3D Subsoil Model of the San Biagio ‘Salinelle’ Mud Volcanoes (Belpasso, Sicily) derived from Geophysical Surveys - S. Imposa; S. Grassi; G. De Guidi; F. Battaglia; G. Lanaia; S. Scudero (Surveys in Geophysics, 2016)

Behavior of Atrazine and Its Degradation Products Deethylatrazine and Deisopropylatrazine in Oxisol Samples - Maristela F. Amadori; Marcio B. Rodrigues; Caio C. Rebouças; Patricio G. Peralta-Zamora; Marco T. Grassi; Gilberto Abate (Water, Air, & Soil Pollution, 2016)

Gokyo Khumbu/Ama Dablam Trek 2012: effects of physical training and high-altitude exposure on oxidative metabolism, muscle composition, and metabolic cost of walking in women - E. Tam; P. Bruseghini; E. Calabria; L. Dal Sacco; C. Doria; B. Grassi; T. Pietrangelo; S. Pogliaghi; C. Reggiani; D. Salvadego; F. Schena; L. Toniolo; et al. (European Journal of Applied Physiology, 2016)

Fusarium spp. is able to grow and invade healthy human nails as a single source of nutrients - J. Galletti; M. Negri; F. L. Grassi; É. S. Kioshima-Cotica; T. I. E. Svidzinski (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

The role of the land use, land use change and forestry sector in achieving Annex I reduction pledges - Giacomo Grassi; Michel G. J. den Elzen; Andries F. Hof; Roberto Pilli; Sandro Federici (Climatic Change, 2012)

Genetic diversity in the endangered Sicilian endemic Brassica rupestris : Proposals for a conservation strategy - F. M. Raimondo; A. Scialabba; G. Zecca; F. Grassi; G. Casazza; L. Minuto (Plant Biosystems, 2012)

Sequence analysis of human rotavirus strains: comparison of clinical isolates from Northern and Southern Italy - T. Grassi; F. Bagordo; A. Cavallaro; M. Guido; C. Malaventura; G. Gabutti; A. Donno (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Allopatric divergence and secondary contacts in Euphorbia spinosa L: Influence of climatic changes on the split of the species - G. Zecca; G. Casazza; L. Minuto; M. Labra; F. Grassi (Organisms Diversity & Evolution, 2011)

Haplotype richness in refugial areas: phylogeographical structure of Saxifraga callosa - F. Grassi; L. Minuto; G. Casazza; M. Labra; F. Sala (Journal of Plant Research, 2009)

Changes in Copper Speciation and Geochemical Fate in Freshwaters Following Sewage Discharges - Fernando F. Sodré; Marco T. Grassi (Water, Air, & Soil Pollution, 2007)

Phylogeographical structure and conservation genetics of wild grapevine - F. Grassi; M. Labra; S. Imazio; R. Ocete Rubio; O. Failla; A. Scienza; F. Sala (Conservation Genetics, 2006)

Chloroplast Microsatellites to Investigate the Origin of Grapevine - S. Imazio; M. Labra; F. Grassi; A. Scienza; O. Failla (Genetic Resources and Crop Evolution, 2006)

Ecogeographic and genetic evaluation of endemic species in the Maritime Alps: the case of Moehringia lebrunii and M. sedoides (Caryophyllaceae) - L. Minuto; F. Grassi; G. Casazza (Plant Biosystems, 2006)

Molecular diversity in Ligurian local races of common bean ( Phaseolus vulgaris L.) - F. Grassi; M. Labra; L. Minuto (Plant Biosystems, 2006)

Genomic stability in Arabidopsis thaliana transgenic plants obtained by floral dip - M. Labra; C. Vannini; F. Grassi; M. Bracale; M. Balsemin; B. Basso; F. Sala (Theoretical and Applied Genetics, 2004)

Ex-situ conservation of Black poplar in Europe: genetic diversity in nine gene bank collections and their value for nature development - V. Storme; A. Vanden Broeck; B. Ivens; D. Halfmaerten; J. Van Slycken; S. Castiglione; F. Grassi; T. Fossati; J. E. Cottrell; H. E. Tabbener; F. Lefèvre; C. Saintagne; et al. (Theoretical and Applied Genetics, 2004)

Evidence of a secondary grapevine domestication centre detected by SSR analysis - F. Grassi; M. Labra; S. Imazio; A. Spada; S. Sgorbati; A. Scienza; F. Sala (Theoretical and Applied Genetics, 2003)

Molecular analysis of natural populations of Populus nigra L. intermingled with cultivated hybrids - T. Fossati; F. Grassi; F. Sala; S. Castiglione (Molecular Ecology, 2003)
In this study six simple sequence repeats (SSR or microsatellites) were selected for their ability to fingerprint a total of 60 commercial clones of Populus deltoides Marsh. and Populus × canadensis Moench (typically derived from crosses between Populus nigra L and P. deltoides ) and to characterize a natural population of P. nigra growing along the Ticino river in the North of Italy. Out of six SSRs used, four microsatellite loci were found to have alleles which were species‐specific to P. deltoides and could therefore be used as markers for introgression of P. deltoides into P. nigra . In the studied region hybrid poplars and P. deltoides commercial clones are cultivated as monoclonal stands close to the area where black poplar has its natural habitat. SSR analysis was performed to investigate whether there was evidence of introgression between the natural population and the monoclonal plantations of hybrids and P. deltoides clones cultivated in the surrounding area. Three stages of the natural population were analysed: a group of old trees about a hundred years old, a younger population (aged 2–30 years) and the seedlings of three females of this population. Alleles specific to P. deltoides were detected only in the old cohort of the natural population, while no introgression was observed in the younger individuals and their progenies. These results were also confirmed by isozyme analysis of loci PGI‐B, PGM and LAP‐A, which were previously identified as diagnostic for P. nigra , P. deltoides and P. × canadensis .

Special Contribution: An Overview of Recent Seismic Refraction Experiments in Central Europe - A. Guterch; M. Grad; A. Špičák; E. Brückl; E. Hegedüs; G.R. Keller; H. Thybo; K. Aric; S. Acevedo; I. Asudeh; M. Behm; A. A. Belinsky; et al. (Studia Geophysica et Geodaetica, 2003)

Structure-effect relationships of amiodarone analogues on the inhibition of thyroxine deiodination - H. R. Ha; B. Stieger; G. Grassi; H. R. Altorfer; F. Follath (European Journal of Clinical Pharmacology, 2000)

5-Hydroxytryptamine blocks the fetal more potently than the adult mouse muscle acetylcholine receptor - F. Grassi (Pflügers Archiv - European Journal of Physiology, 1999)

Gepirone and 1-(2-pyrimidinyl)-piperazine in vitro: human cytochromes mediating transformation and cytochrome inhibitory effects - L. L. von Moltke; D. J. Greenblatt; J. M. Grassi; B. W. Granda; S. M. Fogelman; J. S. Harmatz; S. J. Kramer; L. F. Fabre; R. I. Shader (Psychopharmacology, 1998)

Analysis of magnetic material in the human heart, spleen and liver - P.P. Grassi-Schultheiss; F. Heller; J. Dobson (BioMetals, 1997)